The effect of interval training on the 1500-meter freestyle swimming ability of UNP swimming specialization students - Siregar, Arif Nathanael; Mardesia, Pringgo; Sari, Desi Purnama; Denay, Naluri (Jurnal Patriot, 2025)
Problems: In swimming courses at Padang State University, specifically for specialized swimming, students tend to have difficulty completing the 1500-meter distance event which demands aerobic endurance, technical efficiency, and the ability to regulate swimming rhythm. The difficulties experienced by students are due to limited endurance and ineffective training methods. Therefore, this study examines how interval training can affect long-distance swimming abilities for swimming specialty students. Purpose: This study aims to determine the effect of interval training on the 1500-meter freestyle swimming ability of swimming specialty students at Padang State University. Methods: This study uses a quantitative method with a quasi-experimental design (one group pretest–posttest design). The research sample consisted of 7 students taken using a saturated sampling technique. The research instrument was a 1500-meter freestyle swimming test with travel time measurements. Data were analyzed using the Shapiro–Wilk normality test and a paired sample t-test hypothesis test. Results: The results showed a significance value of 0.003 (p <0.05), which means there is a significant effect of interval training on the 1500-meter freestyle swimming ability. Conclusion: Interval training has been proven to have a significant effect on improving 1500-meter freestyle swimming ability in students specializing in swimming. Therefore, interval training is recommended to be integrated into the training periodization program for swimming specialists.